2021
DOI: 10.1111/1348-0421.12877
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of ALDH1A1 gene polymorphisms associated with antituberculosis drug‐induced liver injury in western Chinese Han population

Abstract: Antituberculosis drug-induced liver injury (ATDILI) has received increasing attention globally, which may limit the effectiveness of antituberculosis (anti-TB) treatment. Many host genetic determinants of ATDILI have been identified recently. As little knowledge is currently available about the association between aldehyde dehydrogenase 1 family member A1 (ALDH1A1) polymorphisms and ATDILI, the association between their variants and the susceptibility to ATDILI was investigated. A total of 747 patients with TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…An additional 15% changed to the form of metabolites. EMB is partially inactivated by oxidation to an aldehyde intermediate, which is converted to the decarboxylic acid derivative assisted by a metabolic enzyme called aldehyde dehydrogenase 1 (ALDH1) ( Figure 2 ) ( PEETS et al, 1965 ; Peng et al, 2021 ). Other drug-metabolizing enzymes (DMEs), such as c ytochrome (CYP), also play a role in the metabolic rate of EMB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 15% changed to the form of metabolites. EMB is partially inactivated by oxidation to an aldehyde intermediate, which is converted to the decarboxylic acid derivative assisted by a metabolic enzyme called aldehyde dehydrogenase 1 (ALDH1) ( Figure 2 ) ( PEETS et al, 1965 ; Peng et al, 2021 ). Other drug-metabolizing enzymes (DMEs), such as c ytochrome (CYP), also play a role in the metabolic rate of EMB.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic polymorphisms can change the pharmacokinetic profile of EMB, such as creatinine clearance, plasma concentration, and drug exposure, and result in the possibility of toxicity or drug resistance ( Table 1 ). Genes that are included in this category are genes that encode ATP-binding cassette (ABC transporter), solute carrier family (SLC transporter), metabolizer enzymes; cytochrome (CYP), UDP-glucuronosyltransferase (UGT), aldehyde dehydrogenase (ALDH), glutathione S-transferase (GST), vitamin D receptor (VDR), pregnane X receptor (PXR), and genes related to optic neuropathy ( Takahashi et al, 2008 ; Ramachandran and Swaminathan, 2012 ; Fatiguso et al, 2016 ; Pontual et al, 2017 ; Sun et al, 2019 ; Peng et al, 2021 ) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al. demonstrated that rs7852860 variants of the ALDH1A1 gene were associated with susceptibility to anti-tuberculosis drug-induced liver injury ( 96 ).…”
Section: Aldh1a1 Overexpression Is An Oncogenic Factor In Most Cancersmentioning
confidence: 99%
“…CA genotype and C allele of rs7852860 were found notably associated with the risk of developing ATDILI. (Peng et al 2021)…”
Section: Cyp7a1mentioning
confidence: 99%